3-Methyl-3,4-dihydro-9H-carbazol-1(2H)-one - Thomas Gunaseelan, A. (International Union of Crystallography, 2009)
In the title molecule, C(13)H(13)NO, the dihedral angle between the benzene ring and the fused pyrrole ring is 2.03 (5)°. The methyl group at the 3-position has an equatorial orientation. The cyclohexene ring adopts an envelope conformation. Three C atoms of the cyclohexene ring, with their attached H atoms, and all atoms of the methyl group are disordered over two positions, the site-occupancy factors being 0.883 (2) and 0.117 (2). In the crystal structure, molecules are stabilized by intermolecular N—H⋯O hydrogen bonds. A C—H⋯π interaction, involving the benzene ring, is also found.